Lifestyle of women with cancer. Part III. Impact of cancer on mental health of women - Pietryka-Michałowska, Elżbieta; Szymańska, Jolanta; Jurkowska, Barbara (Polish Journal of Public Health, 2010)
Introduction. Any disease, a neoplastic one in particular, shatters the internal and external order of the affected woman who has to face new, earlier unknown situations. The commonest negative emotions felt are: fear, depression, anger, stress and anxiety about further functioning in the family and social or professional life.Aim. The main objective of the study was to analyse the emotional state of women with cancers and effects of some factors on their emotional state.Material and methods. The impact of age, place of residence, education, marital status and methods of treatment on mental health of patients with neoplastic diseases was assessed.Results. Fear is the commonest emotional state accompanying cancer patients since the onset of disease. The emotional state of women suffering from cancers is determined by age, place of residence, marital status and the method of treatment applied. Surgery is most strongly associated with low self-esteem. In some cases, the surgical method is such a dramatic experience that it may lead to severe depression.